Jonathan Trumbull papers - Trumbull, Jonathan, 1710-1785.
Photocopy of an ALS (1775 June 20) written by Trumbull to Artemas Ward relating to his order that Connecticut troops be subordinate to the commands of the Continental Army; photocopy of an ALS (1779 August 31) written by Trumbull to Joan Derk van der Capellen (1779 August 31) reporting on the progress of the Revolution and comparing the American struggle for liberty to that of the Dutch; commission (1783 October 15) of Robert Whitford as an officer in the Connecticut militia; and printed matter (1846, 1859) relating to Trumbull's correspondence with van der Capellen.
In part, positive and negative photocopies.
Jurist, merchant, state legislator, and governor of Connecticut.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Capellen, Joan Derk van der, -- 1741-1784 -- Correspondence; Ward, Artemas, -- 1727-1800 -- Correspondence; Whitford, Robert, -- active 1783.; United States. -- Continental Army; Connecticut -- History -- Revolution, 1775-1783.; Connecticut -- Militia; Netherlands -- History -- 1714-1795.; Netherlands -- Politics and government -- 1714-1795; United States -- History -- Revolution, 1775-1783.; Governors -- Connecticut; Jurists; Legislators -- Connecticut; Merchants